Generalized Sasakian-space-forms with a contact conformal curvature tensor - Sudhakar Kumar Chaubey; Sunil Yadav; Mehmet Akif Akyol (Surveys in Mathematics and its Applications)
The present paper deals with the study of generalized Sasakian-space-forms. We show that the Ricci operator commutes with φ. The necessary and sufficient conditions for the Ricci and φ-contact conformally flat generalized Sasakian-space-forms are proved. We validate our results by providing a non-trivial example of a generalized Sasakian-space-form.